Structure and function of retinal ganglion cells in subjects with a history of repeated traumatic brain injury - Klimo, Kelly R.; Stern-Green, Elizabeth A.; Shelton, Erica; Day, Elizabeth; Jordan, Lisa; Robich, Matthew; Racine, Julie; McDaniel, Catherine E.; VanNasdale, Dean A.; Yuhas, Phillip T. (Frontiers in Neurology, 2022)
This study tested whether repeated traumatic brain injuries (TBIs) alter the objective structure or the objective function of retinal ganglion cells (RGCs) in human subjects recruited from an optometry clinic. Case subjects (n = 25) with a history of repeated TBIs (4.12 ± 2.76 TBIs over 0-41 years) and healthy pair-matched control subjects (n = 30) were prospectively recruited. Retinal nerve fiber layer (RNFL) thickness was quantified with spectral-domain optical coherence tomography, and scanning laser polarimetry measured RNFL phase retardation. Measurements of the photopic negative response were made using full-field flash electroretinography. There was no statistically significant difference (p = 0.42) in global RNFL thickness between the case cohort (96.6 ± 9.4 microns) and the control cohort (94.9 ± 7.0 microns). There was no statistically significant difference (p = 0.80) in global RNFL phase retardation between the case cohort (57.9 ± 5.7 nm) and the control cohort (58.2 ± 4.6 nm). There were no statistically significant differences in the peak time (p = 0.95) of the PhNR or in the amplitude (p = 0.11) of the PhNR between the case cohort (69.9 ± 6.9 ms and 24.1 ± 5.1 µV, respectively) and the control cohort (70.1 ± 8.9 ms and 27.8 ± 9.1 µV, respectively). However, PhNR amplitude was more variable (p < 0.025) in the control cohort than in the case cohort. Within the case cohort, there was a strong positive (r = 0.53), but not statistically significant (p = 0.02), association between time since last TBI and PhNR amplitude. There was also a modest positive (r = 0.45), but not statistically significant (p = 0.04), association between time since first TBI and PhNR amplitude. Our results suggest that there were no statistically significant differences in the objective structure or in the objective function of RGCs between the case cohort and the control cohort. Future large, longitudinal studies will be necessary to confirm our negative results and to more fully investigate the potential interaction between PhNR amplitude and time since first or last TBI.